Affidavits - Shaw, G. F. (Statistical and Social Inquiry Society of Ireland, 1869)
Whether it is that I am sadly deficient in the bump of veneration, or that I belong to that class who, we are told, rush in where angels and Members of Parliament fear to tread, I am going tonight to intrude into this high and holy place from which the Commissioners were warned off; to raise the awful veil which shrouds the venerable mystery of legal swearing, and to ask some plain questions, and give what may be considered, no doubt, some presumptuous answers as to the operation and effect of this system.
Read, Tuesday, 28th April, 1868
Keywords: Affidavits; Swearing system in Ireland; Legal oaths; 314.15